2012
DOI: 10.1029/2012ja018010
|View full text |Cite
|
Sign up to set email alerts
|

Comparing VHF coherent scatter from the radar aurora with incoherent scatter and all‐sky auroral imagery

Abstract: [1] VHF coherent scatter radar observations of an auroral substorm over Alaska are analyzed in the context of multibeam incoherent scatter plasma density and drifts data and green-line all-sky optical imagery. Coherent scatter arises from Farley Buneman waves which are excited in the E region whenever the convection electric field is greater than about 20 mV/m. Aperture synthesis radar imaging and other aspects of the methodology facilitate the precise spatial registration of the coherent scatter with coincide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 38 publications
4
47
0
Order By: Relevance
“…The two representations would be exactly analogous if all convection drift speeds were 350 m/s. Both are reminiscent of the results in the recent study by Hysell et al [] in which a reasonable agreement was obtained between the convection component measured by the Poker Flat incoherent scatter radar (PFISR) and the convection component implied by their coherent velocity measurements at 30 MHz and their assumed relationship Vph=Vcos()θθ, where V ∘ =350 + ( V E /100) 2 in meters per second and θ ∘ is a small offset due to thermal effects. The above expression for the phase velocity has been suggested by experimental results of Bahcivan et al [] in the form with C s = V ∘ , which was further supported by simulations [ Oppenheim et al , ; Oppenheim and Dimant , ].…”
Section: Discussionsupporting
confidence: 84%
“…The two representations would be exactly analogous if all convection drift speeds were 350 m/s. Both are reminiscent of the results in the recent study by Hysell et al [] in which a reasonable agreement was obtained between the convection component measured by the Poker Flat incoherent scatter radar (PFISR) and the convection component implied by their coherent velocity measurements at 30 MHz and their assumed relationship Vph=Vcos()θθ, where V ∘ =350 + ( V E /100) 2 in meters per second and θ ∘ is a small offset due to thermal effects. The above expression for the phase velocity has been suggested by experimental results of Bahcivan et al [] in the form with C s = V ∘ , which was further supported by simulations [ Oppenheim et al , ; Oppenheim and Dimant , ].…”
Section: Discussionsupporting
confidence: 84%
“…These spectral images predict that the flow angle of density irregularities driven by the pure FBI should increase with altitude. Quantitatively, the calculated centroid angles in all six panels of Figure 5 are larger than the value of −10 • that Uspensky et al (2003) and Hysell et al (2012) assume. This result is qualitatively consistent with the conclusion of Uspensky et al (2003) that the ion drift contribution to the relative drift velocity is important.…”
Section: 1029/2019ja027326mentioning
confidence: 63%
“…The angle between Journal of Geophysical Research: Space Physics 10.1029/2019JA027326 these two drifts is the flow angle. Hysell et al (2012) reported results from VHF coherent-scatter radar observations during a geomagnetic substorm over Alaska, with an emphasis on aspects of the radar aurora revealed through VHF radar imaging. Haldoupis et al (1984) also used STARE to make observations of a common volume in the high-latitude E-region.…”
Section: Introductionmentioning
confidence: 99%
“…To incorporate flow angle effects into the heuristic model, we model the phase velocities and flow angles in terms of the Doppler spectral moments (Hysell et al, ): ds1em=vphcosfalse(θθ0false)+vn, dω1em=αvphfalse|sinfalse(θθ0false)false|. …”
Section: Estimation Of Flows From Spectral Datamentioning
confidence: 99%